Al-Ṭayyibât and Al-Khâbisât in QS. al-Nur: 26: Comparative Insights from Ibn Jarir and Quraish Shihab - Djuned, Muslim (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
The terms al-Ṭayyibât and al-Khâbisât in QS. al-Nur: 26 have long been central to discussions on Islamic marital ethics, particularly the principle of compatibility (kafa’ah) in moral and spiritual values. This study examines the interpretations of these terms by two prominent scholars: Ibn Jarir al-Thabari, representing classical exegesis, and Muhammad Quraish Shihab, offering a contemporary perspective. Using a comparative and descriptive-analytical approach, the research highlights key differences in their methodologies and contextual applications. Al-Thabari’s interpretation, rooted in asbab al-nuzul and linguistic precision, confines the meaning of al-Ṭayyibât and al-Khâbisât to speech, primarily defending the moral purity of Aisha RA against slander. In contrast, Quraish Shihab broadens the scope to include actions, behaviors, and character, emphasizing the principle of compatibility in relationships. This study finds that while Al-Thabari’s approach focuses on historical textuality, Shihab integrates socio-ethical considerations to address the practical challenges of modern marriage. The findings bridge classical scholarship and contemporary application, contributing to a nuanced understanding of QS. al-Nur: 26 and its relevance to marital ethics.